Faculty Perspectives: The Diffusion of Competency-Based Education - Kristi Archuleta Frush (Adult Education Research Conference, 2014)
This roundtable is a dialogue of faculty perspectives concerning competencybased education. Adult educators facilitating in graduate programs may want to pay close attention to the transformation across the nation related to degree completion as many of our learners will be at the forefront of addressing these issues and implementing change.